Long-term relationship between everolimus blood concentration and clinical outcomes in Japanese patients with metastatic renal cell carcinoma: a prospective study - Shinya Takasaki; Hiroaki Yamaguchi; Yoshihide Kawasaki; Masafumi Kikuchi; Masaki Tanaka; Akihiro Ito; Nariyasu Mano (Journal of Pharmaceutical Health Care and Sciences, 2019)
Abstract Background Everolimus is an oral inhibitor of mammalian target of rapamycin, approved for metastatic renal cell carcinoma (mRCC). Recently, personalized medicine through therapeutic drug monitoring (TDM) is recommended in cancer therapy. In this study, the relationship between everolimus blood concentration and clinical outcomes on a long-term were evaluated in Japanese patients with mRCC. Methods Patients with mRCC were enrolled following treatment with everolimus at Tohoku University Hospital between April 2012 and December 2016. The relationship between everolimus trough blood concentration on day 8 of everolimus therapy and just before discontinuation or dose reduction, and their adverse events were evaluated. Patients were divided into two groups based on the median of everolimus blood concentration on day 8 of treatment, and the profiles of adverse events, and efficacy [time to treatment failure (TTF) and progression-free survival (PFS)] were evaluated. Results The median (range) everolimus blood concentrations on day 8 after starting everolimus administration and just before discontinuation or dose reduction were 15.3 (8.1–28.0) ng/mL and 14.8 (6.4–58.4) ng/mL, respectively, with no significant difference between these values (P = 0.3594). Patients (n = 6) with discontinuation or dose reduction following adverse events in everolimus therapy had significantly higher blood concentrations than patients (n = 4) with dose maintenance on both day 8 (median, 18.0 vs 8.2 ng/mL; P = 0.0139) and just before discontinuation or dose reduction (median, 22.9 vs 9.7 ng/mL; P = 0.0142). Median TTF and PFS of the total patients (n = 10) were 96 days (95% confidence interval [CI], 26–288) and 235 days (95% CI, 28–291), respectively. Subgroup analysis showed that TTF of the patients with > 15.3 ng/mL (n = 5) was not significantly different from that of the patients with ≤15.3 ng/mL (n = 5; P = 0.5622). Similarly, PFS of the patients with > 15.3 ng/mL was not significantly different from that of the patients with ≤15.3 ng/mL (P = 0.3436). Conclusions This study demonstrated the long-term relationship between everolimus blood level and clinical outcomes and adverse events in Japanese patients with mRCC. Thus, TDM in everolimus therapy could be a useful tool for the early prediction of adverse events for Japanese patients with mRCC.